2001
DOI: 10.1074/jbc.m010495200
|View full text |Cite
|
Sign up to set email alerts
|

Interactions within the Coiled-coil Domain of RetGC-1 Guanylyl Cyclase Are Optimized for Regulation Rather than for High Affinity

Abstract: RetGC-1, a member of the membrane guanylyl cyclase family of proteins, is regulated in photoreceptor cells by a Ca 2؉ -binding protein known as GCAP-1. Proper regulation of RetGC-1 is essential in photoreceptor cells for normal light adaptation and recovery to the dark state. In this study we show that cGMP synthesis by RetGC-1 requires dimerization, because critical functions in the catalytic site must be provided by each of the two polypeptide chains of the dimer. We also show that an intact ␣-helical coiled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(151 citation statements)
references
References 67 publications
7
144
0
Order By: Relevance
“…2C), the basal RetGC activity in washed membranes that lack GCAPs remains insensitive to Ca 2ϩ at all tested concentrations of Mg 2ϩ . Mg 2ϩ needs to be present as a part of Mg-GTP substrate complex in the catalytic center of RetGC and is essential for its activity (27); therefore, the decrease in RetGC activity at [Mg] f below 1 mM (Fig. 2D) could be explained by a decrease in concentration of Mg-GTP substrate complex (inset on Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2C), the basal RetGC activity in washed membranes that lack GCAPs remains insensitive to Ca 2ϩ at all tested concentrations of Mg 2ϩ . Mg 2ϩ needs to be present as a part of Mg-GTP substrate complex in the catalytic center of RetGC and is essential for its activity (27); therefore, the decrease in RetGC activity at [Mg] f below 1 mM (Fig. 2D) could be explained by a decrease in concentration of Mg-GTP substrate complex (inset on Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GCAP1 Binding to the Cyclase Does Not Equal Target Activation, as GCAP1 Activates RetGC by a Two-step MechanismRetGC1 is active as a homodimer, because the two active sites in the catalytic domain of the enzyme are formed by two catalytic subunits, each providing one Mg 2ϩ binding and one GTP binding site for the two complementing each other active sites (45,63). The binding of GCAP1 enhances RetGC dimerization in the complex to promote cyclase activation (64).…”
Section: Gcap1-gfp Pccmentioning
confidence: 99%
“…The biochemical studies of CORD6 mutations in ReGC1 pioneered by J. Hurley's group (44,45) demonstrated that Arg 838 substitutions alter Ca 2ϩ sensitivity of RetGC regulation by affecting coiled-coil interactions in the cyclase dimerization domain. Although RetGC1 is not a calcium-sensitive protein, the dimerization domain is part of the GCAP1 and GCAP2 binding interface (59 -61), therefore, change in its structure unbalances RetGC1 affinities for two competing with each forms of GCAP1, Mg 2ϩ -liganded (activator) and Ca 2ϩ -liganded (inhibitor) (46).…”
Section: What Processes Downstream Of the Mutated Cord6 Retgc1 Cause mentioning
confidence: 99%
“…Among the genes linked to CORD6 in multiple genetic studies (34,45,51,52), GUCY2D coding for a human RetGC1 has been found most frequently affected by substitutions in codon 838 replacing , were shown to cause a prominent shift in Ca 2ϩ sensitivity of the cyclase regulation by GCAP1 when heterologously expressed in cultured HEK293 (44 -46). However, the physiological effects of the Arg 838 substitutions in RetGC1 have not been demonstrated in mammalian photoreceptors.…”
Section: The Arg 838 Mutation In Retgc1 Alters Physiology Of Photorecmentioning
confidence: 99%